Cross‐reactivity between methylisothiazolinone, octylisothiazolinone and benzisothiazolinone using a modified local lymph node assay. (26th November 2016) - Schwensen, J.F.; Menné Bonefeld, C.; Zachariae, C.; Agerbeck, C.; Petersen, T.H.; Geisler, C.; Bollmann, U.E.; Bester, K.; Johansen, J.D.
Abstract : What's already known about this topic? Contact allergy to methylisothiazolinone (MI) in the European population is alarmingly high. Retrospective observational studies of patients with contact allergy to MI have shown that concomitant reactions between MI, octylisothiazolinone (OIT) and benzisothiazolinone (BIT) may exist. What does this study add? MI induced a significant concentration‐dependent immune response after a sensitization phase of three consecutive days. MI, OIT and BIT induced the same concentration‐dependent inflammatory response with proliferation of CD4 + and CD8 + T cells, and partly CD19 + B cells, in MI‐sensitized mice. Cross‐reactivity was seen between MI and OIT and between MI and BIT when the potency of the chemical was taken into account in the choice of challenge concentration. Plain language summary available online Summary: Background: In the light of the exceptionally high rates of contact allergy to the preservative methylisothiazolinone (MI), information about cross‐reactivity between MI, octylisothiazolinone (OIT) and benzisothiazolinone (BIT) is needed. Objectives: To study cross‐reactivity between MI and OIT, and between MI and BIT. Methods: Immune responses to MI, OIT and BIT were studied in vehicle and MI‐sensitized female CBA mice by a modified local lymph node assay. The inflammatory response was measured by ear thickness, cell proliferation of CD4 + and CD8 + T cells, and CD19 + B cells in the auricular draining lymph nodes. Results: MI induced significant, strong, concentration‐dependent immune responses in the draining lymph nodes following a sensitization phase of three consecutive days. Groups of MI‐sensitized mice were challenged on day 23 with 0·4% MI, 0·7% OIT and 1·9% BIT – concentrations corresponding to their individual EC3 values. No statistically significant difference in proliferation of CD4 + and CD8 + T cells was observed between mice challenged with MI compared with mice challenged with BIT and OIT. Conclusions: The data indicate cross‐reactivity between MI, OIT and BIT, when the potency of the chemical was taken into account in choice of challenge concentration. This means that MI‐sensitized individuals may react to OIT and BIT if exposed to sufficient concentrations.